Examining the Influence of E-Service Quality in E-commerce on Customers' Repurchase Intentions in Mekarwangi Village, West Java: A Rasch Model Perspective - Perdana, Yoga; Pamungkas Gautama, Budhi; Miftahuddin, Asep; Salsabila Sidiq, Aina; Maulid, Dibias Lazuardi (Fakultas Pendidikan Ekonomi dan Bisnis, 2023)
The research presented in this article investigates the impact of E-commerce E-Service Quality on Product Repurchase Intentions in Mekarwangi Village, West Bandung Regency. The study was conducted with a sample of 20 frequent users of the E-Commerce application in Mekarwangi Village, analyzed using the Rasch Model. The results indicate that E-service quality does not have a significant influence on customers' intentions to repurchase products through their chosen E-commerce platform. Despite the presence of certain subpar E-Services, customers continue to utilize the E-Commerce platform.